A comparative study of Alvarado and RIPASA scoring systems in diagnosis of acute appendicitis - Varma, Ankur; Varshney Varma, Aditi; Joseph, Jebin (International Surgery Journal, 2019)
Background: Acute appendicitis is a diagnostic dilemma for surgeons due to wide array of differential diagnosis and sometimes due to atypical presentation. Diagnosis using sonography, which is the most common modality, has a very low specificity and sensitivity. In such cases it puts a surgeon in dilemma especially in an emergency setting. The integration of clinical scores into the diagnostic process in acute appendicitis has been shown to improve decision making and reducing the negative appendectomy. Methods: This is a prospective observational study attempted to compare the efficiency of Alvarado and Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) score, in pre-operative diagnosis of acute appendicitis and to correlate these scores with histo-pathological diagnosis.100 cases satisfying inclusion and exclusion criteria were selected for study. Based on detailed history and thorough clinical examination, diagnosis of acute appendicitis was made. Results: Sensitivity for detecting acute appendicitis was found to be higher using RIPASA score. Negative appendectomy rate by RIPASA and Alvarado scoring systems were 11.5 and 19.2% meanwhile it was 12% with sonography. Conclusions: In the diagnosis of acute appendicitis, clinical scoring is a fast, simple, reliable, non-invasive, repeatable and safe diagnostic modality without extra expense and complications. This study shows RIPASA is a better scoring system than Alvarado in the diagnosis of acute appendicitis.